Central Bank Credit to the Government : What Can We Learn From International Practices? - Matamoros-Indorf, Marcela (IMF Working Papers; Working Paper, 2012)
Using a central bank legislation database, this paper documents and analyzes worldwide institutional arrangements for central bank lending to the government and identifies international practices. Key findings are: (i) in most advanced countries, central banks do not finance government expenditure; (ii) in a large number of emerging and developing countries, short-term financing is allowed in order to smooth out tax revenue fluctuations; (iii) in most countries, the terms and conditions of these loans are typically established by law, such that the amount is capped at a small proportion of annual government revenues, loans are priced at market interest rates, and their maturity falls within the same fiscal year; and (iv) in the vast majority of countries, financing other areas of the state, such as provincial governments and public enterprises, is not allowed. The paper does not address central banks' financial support during financial crises.